2014
DOI: 10.2527/jas.2013-7505
|View full text |Cite
|
Sign up to set email alerts
|

Meal frequency changes the basal and time-course profiles of plasma nutrient concentrations and affects feed efficiency in young growing pigs1

Abstract: Ingested dietary nutrients and feed energy are partitioned among tissues to sustain body growth. Based on the respective costs of the various metabolic pathways allowing use and storage of feed energy into cells, it may be theorized that daily meal frequency could affect growth, body composition or feed efficiency. This study aimed to determine the effects of daily meal frequency on nutrient partitioning, tissue metabolism and composition, and performance. Young growing pigs (30 kg BW) were offered a same amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 37 publications
5
43
1
Order By: Relevance
“…However, conflicting results of meal frequency on BW and fat gain in pigs were observed among previous studies (Friend and Cunningham, ; Allee et al., ; Schneider et al., ). While some experiments showed that increased meal frequency improved growth performance of pigs (Schneider et al., , ), other works reported otherwise (Allee et al., ; Le Naou et al., ). However, Le Naou et al.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, conflicting results of meal frequency on BW and fat gain in pigs were observed among previous studies (Friend and Cunningham, ; Allee et al., ; Schneider et al., ). While some experiments showed that increased meal frequency improved growth performance of pigs (Schneider et al., , ), other works reported otherwise (Allee et al., ; Le Naou et al., ). However, Le Naou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding frequency has been considered as an important factor to affect body weight (BW) gain and fat deposition in animals and human (Schwarz et al., ; Chaix et al., ; Le Naou et al., ). Meal frequency impacts BW gain by regulating the partition and storage of energy (glycogen and lipids), rather than modulating the digestibility and absorption of nutrients in pigs (Leveille, ; Allee et al., ; Chastanet et al., ; Schneider et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations